DDGP followed by radiotherapy vs VIPD followed by radiotherapy in newly diagnosed early NK/T-cell lymphoma. (July 2022) - Zhang, Lei; Shangguan, Chenxing; Li, Xin; Li, Ling; Wang, Xinhua; Fu, Xiaorui; Sun, Zhenchang; Shi, Yonggang; Wu, Jingjing; Zhang, Xudong; Yu, Hui; Nan, Feifei; et al.
Abstract: Purpose: To explore the best treatment for early natural killer/T (NK/T)-cell lymphoma, we compared the efficacy and safety of DDGP (pegaspargase, gemcitabine, cisplatin and dexamethasone) followed by radiotherapy (RT) and VIPD (etoposide, ifosfamide, cisplatin, and dexamethasone) followed by radiotherapy for newly diagnosed patients. Materials and Methods: 40 newly diagnosed patients with stage I-II from January 2011 to November 2016 were treated with DDGP followed by radiotherapy or VIPD followed by radiotherapy. They were assessed in this study. Results: The complete response rate (CRR) and overall response rate (ORR) of the DDGP followed by radiotherapy group were higher than those of the VIPD followed by radiotherapy group (CRR: 85 % vs 50 %, P = 0.018; ORR: 95 % vs 65 %, P = 0.048). The 5-year progression-free survival (PFS) rate was better in the DDGP followed by radiotherapy group (83.3 % vs 44.4 %, χ2 = 7.809, P = 0.005). There was no significant difference in the 5-year overall survival (OS) rate between the two groups (83.0 % vs 72.1 %, χ2 = 0.231, P = 0.631). Treatment method (P = 0.011) and IPI score (P = 0.027) were independent risk factors for PFS. The DDGP followed by radiotherapy group was more prone to grade I-II clotting dysfunction (P = 0.004). Conclusions: In patients newly diagnosed with early NK/T-cell lymphoma, those treated with DDGP followed by radiotherapy had a higher CRR and ORR and longer PFS than those treated with VIPD followed by radiotherapy, and adverse reactions were tolerable. Highlights: Radiotherapy combined with chemotherapy has good results in early ENKTL. DDGP followed by RT had a higher CRR and ORR and longer PFS in early ENKTL. Adverse reactions in DDGP followed by RT group were tolerable. Patients were more likely to progress in VIPD followed by RT group.